Amplification of rabbit hepatocyte growth factor and detection of its expression in COS-7 cell line - Yao, H; Han, J; Wang, J; Wang, L; Gong, C; Li, L; Liang, Z; Tian, Y (Cellular and Molecular Biology, 2015)
We used RT-PCR, nested PCR to acquire the partial 5'- race fragment of rabbit HGF cDNA and the partial 3'- race fragment of rabbit HGF cDNA. Then, we used recombination PCR to acquire rabbit HGF successfully. Homology analysis was conducted among the sequence of RABHGF and known human and rat HGF by DNAStar. It was proved that high level of homology existed among the sequences of those three HGF genes. We used the acquired gene of RABHGF to construct its recombinant eukaryotic expression vector pcDNA3.1(+)-RABHGF (pRABHGF). The identification of the eukaryotic expression vector pRABHGF by PCR, restriction enzyme and sequencing analysis showed that rabbit HGF gene was correctly inserted into the vector. pRABHGF and pcDNA3.1(+) as controls were transfected into COS-7 cells by lipofectamine. It takes 24h-36h after transfection to detect the expression of RABHGF protein by indirect immunofluorescence assay (IFA). The proliferation of cos-7 cells were evaluated by MTT assay. The result displayed positive effect of RABHGF protein on the proliferation of COS-7 cells. This study lays the foundation for a new gene therapy method for ischemic heart disease.